Edukasi Pemanfaatan Media Qreatif Sebagai Media Pembelajaran Interaktif Bagi Orang Tua dan Siswa Sekolah Dasar - Janson Silaban, Patri; Nisa Sarbina; Santa Brigitta Limbong; Dita Vinancia Mariana Tampubolon; Yolanda Santi Munthe; Ryan Alden Tarigan (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This community service activity aims to provide education to parents about the use of Qreatif media as an interactive learning medium in supporting the learning process of elementary school students at home. The background of this activity is that there is still a limited understanding of some parents on the use of learning media that is interesting and able to increase children's motivation to learn. The activity was carried out through socialization, demonstrations, and direct assistance to three parents who have elementary school-age children. The material provided includes an introduction to Qreatif media, how to access and use it, and examples of its application in daily learning activities. Evaluation was carried out through observation and question and answer sessions to find out the level of understanding of participants after participating in the activity. The results of the service showed that parents gained better knowledge and skills in utilizing Qreatif media as an interactive learning medium. In addition, participants showed high enthusiasm and gave positive responses to the use of the media because they were considered able to create a more interesting, fun, and encouraging active learning environment during the learning process. This activity is expected to increase the role of parents in accompanying the children's learning process at home while supporting the creation of more effective and innovative learning.